Pengaruh Electronic Word of Mouth dan Brand Image terhadap Purchase Intention dengan Brand Awareness sebagai Intervening: Studi Pada Produsen Dessert Box - Komariah Ulan; Agung Kresnamurti Rivai P; Dewi Agustin Pratama Sari (Fakultas Ekonomi Universitas Negeri Jakarta, 2022)
The purpose of this study was to see the effect of Electronic Word of Mouth on Brand Awareness, Brand Image on Brand Awareness, Brand Awareness on Purchase Intention, Electronic Word of Mouth on Purchase Intention, Brand Image on Purchase Intention, Brand Awareness mediating E-WOM on Purchase Intention, Brand Awareness mediates Brand Image on Purchase Intention on followers of Bittersweet by Najla Instagram social media in the Jakarta area. The research data was collected by distributing questionnaires to followers of social media Instagram Bittersweet by Najla, domiciled in the Jakarta area. The sample of this study was 250 respondents. Researchers used Lisrel version 8.8 as an SEM application to process and analyze research data. The results of the study show a positive and significant influence between Electronic Word of Mouth on Brand Awareness, Brand Image has a significant effect on Brand Awareness, Brand Awareness has a significant considerable effect on Purchase Intention, Electronic Word of Mouth has a significant influence on Purchase Intention, Brand Image has a significant influence on Purchase Intentions, Brand Awareness has a role as a mediator of the positive and significant relationship between E-WOM and Purchase Intention and Brand Awareness has a role as a mediator of the relationship between Brand Image and Purchase Intention in a positive and significant way in Bittersweet by Najla. Tujuan dari penelitian ini adalah untuk melihat pengaruh Electronic Word of Mouth terhadap Brand Awareness, Brand Image terhadap Brand Awareness, Brand Awareness terhadap Purchase Intention, Electronic Word of Mouth terhadap Purchase Intention, Brand Image terhadap Purchase Intention, Brand Awareness memediasi E-WOM terhadap Purchase Intention, Brand Awareness memediasi Brand Image terhadap Purchase Intention pada pengikut sosial media Instagram Bittersweet by Najla di wilayah Jakarta. Data penelitian dikumpulkan dengan penyebaran kuesioner kepada pengikut sosial media Instagram Bittersweet by Najla yang berdomisili di Wilayah Jakarta dan sampel penelitian ini ialah sebanyak 250 responden. Peneliti menggunakan Lisrel versi 8.8 sebagai aplikasi SEM untuk mengolah dan menganalisis data penelitian. Hasil dari penelitian menunjukkan pengaruh positif dan signifikan antara Electronic Word of Mouth terhadap Brand Awareness, Brand Image berpengaruh signifikan terhadap Brand Awareness, Brand Awareness berpengaruh signifikan pada Purchase Intention, Electronic Word of Mouth memiliki pengaruh signifikan pada Purchase Intention, Brand Image memiliki pengaruh signifikan pada Purchase Intention, Brand Awareness memiliki peran sebagai mediator hubungan antara E-WOM terhadap Purchase Intention secara positif dan signifikan serta Brand Awareness memiliki peran sebagai mediator hubungan antara Brand Image terhadap Purchase Intention secara positif dan signifikan pada Bittersweet by Najla.